Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1097/rlu.0b013e31823eaadb
|View full text |Cite
|
Sign up to set email alerts
|

Different Distribution of 62Cu ATSM and 18F-FDG in Head and Neck Cancers

Abstract: In patients with head-and-neck cancer, intratumoral distribution of Cu-ATSM and FDG showed a negative correlation in SCC and a positive correlation in adenocarcinoma. The 2 tracers represented different pathophysiological microenvironments in different tumors, suggesting that noninvasive hypoxic tissue imaging with Cu-ATSM would be beneficial in the pretreatment evaluation of head-and-neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…8,9 The main advantages of Cu-ATSM over 18 F-labeled nitroimidazoles are faster kinetics and better tumor-to-background contrast, which enables delineation of tumor hypoxia within 1 hour with high contrast. 12,13 These differences suggested that regions of increase in glucose metabolism and hypoxic overreduction microenvironment within the tumor could vary depending on the pathohistology of the tumor and that the identification of regions with distinct biologic characteristics could play a significant role in the clinical diagnosis and therapy planning for HNC and NSCLC patients. 12,13 These differences suggested that regions of increase in glucose metabolism and hypoxic overreduction microenvironment within the tumor could vary depending on the pathohistology of the tumor and that the identification of regions with distinct biologic characteristics could play a significant role in the clinical diagnosis and therapy planning for HNC and NSCLC patients.…”
Section: F-fmiso In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 The main advantages of Cu-ATSM over 18 F-labeled nitroimidazoles are faster kinetics and better tumor-to-background contrast, which enables delineation of tumor hypoxia within 1 hour with high contrast. 12,13 These differences suggested that regions of increase in glucose metabolism and hypoxic overreduction microenvironment within the tumor could vary depending on the pathohistology of the tumor and that the identification of regions with distinct biologic characteristics could play a significant role in the clinical diagnosis and therapy planning for HNC and NSCLC patients. 12,13 These differences suggested that regions of increase in glucose metabolism and hypoxic overreduction microenvironment within the tumor could vary depending on the pathohistology of the tumor and that the identification of regions with distinct biologic characteristics could play a significant role in the clinical diagnosis and therapy planning for HNC and NSCLC patients.…”
Section: F-fmiso In Humansmentioning
confidence: 99%
“…12,13 Thus, an average image of the last 10-minute frame, considered to be appropriate scan timing for the tracer retention phase from the TACs, was used to evaluate tumor hypoxic tissues. 12,13 Thus, an average image of the last 10-minute frame, considered to be appropriate scan timing for the tracer retention phase from the TACs, was used to evaluate tumor hypoxic tissues.…”
Section: Image Analysismentioning
confidence: 99%
“…The short-lived radionuclides can be used for sequential measurements, whereas radionuclides with longer half lives do Table 2 for full names. Lewis et al [133] , Yuan et al [134] , Kersemans et al [135] , Matsumoto et al [136] Ballegeer et al [137] , Bowen et al [138] , Lewis et al [133] , Myerson et al [139] , O'Donoghue et al [72] Ballegeer et al [137] , Hansen et al [140] , Matsumoto et al [136] , McCall et al [66] , O'Donoghue et al [72] , Oh et al [74] , Yuan et al [134] Grigsby et al [141] , Tateishi et al [142] , Valtorta et al [143] , Weeks et al [144] Dence et al [145] , Kersemans et al [135] , Lewis et al [146] , Matsumoto et al [136] , O'Donoghue et al [72] Dehdashti et al [86] , Lohith et al [67] , Wong et al [80] , Zhang et al [81] Chao et al [147] , Dehdashti et al [148] , Dehdashti et al [149] , Dietz et al [150] , Grassi et al [151] , Grigsby et al [141] , Kositwattanarerk et al [152] , Laforest et al [153] , Lewis et al [154] , Minagawa et al [155] , Nyflot et al [156] [ Mahy et al [158] , Mahy et al …”
Section: F]fetnim and [mentioning
confidence: 99%
“…Tolerability of ATSM and GTSM is implied by their use in various clinical settings and animal experiments (14,17) and was confirmed by us on mouse peritoneal macrophages (Fig. 3), which were obtained according to published protocols (18).…”
mentioning
confidence: 99%